2019
DOI: 10.1016/j.chiabu.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Signs of attachment disorders and social functioning among early adolescents with a history of institutional care

Abstract: Background: Institutional rearing is associated with increased risk for reactive attachment disorder (RAD) and disinhibited social engagement disorder (DSED). Disorders of attachment involve disturbances in children's primary caregiving relationships, and are likely to disturb multiple domains of social functioning. Objective: To examine associations between signs of RAD and DSED and social functioning in early adolescence. Participants and setting: Our participants were 110 children with a history of institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 45 publications
1
22
0
1
Order By: Relevance
“…However, unlike noninstitutionalized youth who tend to become withdrawn or socially avoidant following victimization, postinstitutionalized youth demonstrate significantly more disinhibited behavior (Pitula et al, 2014). This is consistent with recent work from our group that shows higher levels of disinhibited social engagement disorder among institutionally-reared children which is, in turn, related to lower social competence (Guyon-Harris, Humphreys, Fox, Nelson, & Zeanah, 2018, 2019. While not a primary goal of the current study, supplementary analysis showed that more SC difficulties at age 8 (and to a lesser extent at age 16) are related to multiple behavioral problems at age 16, including signs of disinhibited social engagement disorder, reactive attachment disorder, and ADHD, even after controlling for general psychopathology risk (Table S8).…”
Section: Discussionsupporting
confidence: 89%
“…However, unlike noninstitutionalized youth who tend to become withdrawn or socially avoidant following victimization, postinstitutionalized youth demonstrate significantly more disinhibited behavior (Pitula et al, 2014). This is consistent with recent work from our group that shows higher levels of disinhibited social engagement disorder among institutionally-reared children which is, in turn, related to lower social competence (Guyon-Harris, Humphreys, Fox, Nelson, & Zeanah, 2018, 2019. While not a primary goal of the current study, supplementary analysis showed that more SC difficulties at age 8 (and to a lesser extent at age 16) are related to multiple behavioral problems at age 16, including signs of disinhibited social engagement disorder, reactive attachment disorder, and ADHD, even after controlling for general psychopathology risk (Table S8).…”
Section: Discussionsupporting
confidence: 89%
“…Other forms of psychopathology that are known to be associated with the absence of adequate caregiving, specifically reactive attachment disorder and disinhibited social engagement disorder (DSED; American Psychiatric Association, 2013), have been examined as potential correlates or predictors of social functioning in children with institutional care exposure (Guyon-Harris, Humphreys, Fox, Nelson, & Zeanah, 2018b; Sonuga-Barke et al, 2010). However, symptoms of these disorders are relatively rare in later childhood and early adolescence (Gleason et al, 2011; Guyon-Harris et al, 2018; Guyon-Harris, Humphreys, Fox, Nelson, & Zeanah, 2018a).…”
mentioning
confidence: 99%
“…The rst item explained 51.83% (factor loading = 0.76), the second explained 28.80% (factor loading = .80) and the third item explained 19.37% (factor loading = .51) of the variance in this pictorial Secure Base Script knowledge test. All three items thus reach factor loadings above 40,. which is argued as acceptable for measures with such a small number of items [58].…”
mentioning
confidence: 83%